Factors that Influence Student Interest in Participating in the Independent Program to Learn an Independent Campus (MBKM) (Study on The Accounting Department of the Faculty of Economics and Business, University of Mataram) - Lestari, Baiq Anggun Hilendri; Jumaidi, Lalu Takdir; Inapty, Biana Adha; Cahyani, Regita (PT FORMOSA CENDEKIA GLOBAL, 2024)
Finding out what influences students' desire to take part in the Merdeka Belajar-Kampus Merdeka (MBKM) program is the aim of this study. This study employs a descriptive research design and a qualitative methodology. Observational interviews and the distribution of Google Forms surveys served as the methods for gathering data. Through the processes of data reduction, presentation, and conclusion drawing, the data analysis employed descriptive storytelling methodologies. According to the findings, 1) internal characteristics, such as students' knowledge level and desire and motivation for the MBKM program, have an impact on their interest in enrolling in the program. Students' desire to engage in MBKM is influenced by external factors such as peer pressure and the social environment. 3) Pleasurable feelings are a result of emotional components that lead to interest and satisfaction. The survey's findings demonstrate how enthusiastic students are about the MBKM program.